Defining Information Policy in the Canadian Context - Dowding, Martin; Nilsen, Kirsti (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Over the last decade or so we have witnessed in Canada, as elsewhere, a growing wave of policy developments and discussion sin response to new information and communication technologies. It has been noted that such information policy discourse suffers from a lack of clear consensus on what constitutes its true boundaries. This paper proposes to map the boundaries of Information Policy. . .